(3TQM JLQjO GdYbGFOs - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdbGgQ SdWGfg s
(3BNQgG (B:s
(3Je cJGHI GdcJGHq s
(3GdfSNI HgG MhGTs
(3HgG JYbjHI ZjQ efJXeIs
(3JLQjO GdYbGFO ddWhSis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdadSaI hGdefWbs